2015
DOI: 10.1039/c5cp05531h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of branched Pd nanocrystals with tunable structures, their growth mechanism, and enhanced electrocatalytic properties

Abstract: Branched Pd nanocrystals (NCs) with tunable architectures are synthesized in high yields (>95%) by simply adjusting the concentration of H2PdCl4 in the presence of fixed amounts of cetyltrimethylammonium bromide (CTAB), L-ascorbic acid (L-AA), and CuBr2(-) that is produced by reducing CuBr2 with L-AA. The as-synthesized branched Pd NCs have long, straight branches with thin diameters. At the same time, the growth process of the branched Pd NCs is monitored, which provides mechanistic insights for the branching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…This preliminary study is in-line to those carried out by other groups with similar samples. 32,57,58 While the capping ligands employed during a NC synthesis are key to shape-control and preventing aggregation, they can also be detrimental to the catalytic activity by blocking access of reactant molecules to the active surface atoms. Therefore, it is of the highest importance to 'clean' the NC surfaces without inducing structural changes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This preliminary study is in-line to those carried out by other groups with similar samples. 32,57,58 While the capping ligands employed during a NC synthesis are key to shape-control and preventing aggregation, they can also be detrimental to the catalytic activity by blocking access of reactant molecules to the active surface atoms. Therefore, it is of the highest importance to 'clean' the NC surfaces without inducing structural changes.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the formation of highly branched nanostructures requires growth under conditions that typically favour kinetic products. To date, a range of branched nanostructures have been synthesized for various noble metals, including Pt, [27][28][29] Pd, 3,[30][31][32] Au, 33,34 Ag, 35 and Ru. 36 However, the fast rate of kinetically controlled growth makes it difficult to control the final particle size, with branched structures >100 nm being produced.…”
Section: -26mentioning
confidence: 99%
“…b-Pd-NCs core was prepared following our previous work and the representative characterization results are presented in Fig. S1 in the Supplementary Materials 40 . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetically controlled overgrowth is based on regulation of the growth rate at which atoms are generated and added to the surface of a seed, and the final products obtained from kinetically controlled overgrowth are not limited by thermodynamic confinement, allowing for the formation of NCs with polyhedral structure. Experimentally, the kinetically controlled overgrowth involved in synthesis of polyhedral Pd NCs can be achieved by adjusting a series of parameters, including the concentrations of Pd precursor, the reaction temperature, the introduction of ionic species, or a combination of them [58][59][60] . For example, Tilley et al 61 have reported the synthesis of highly branched Pd NCs with a combination of {113}, {115}, and {220} high-index facets on the surface by using oleylamine (OAm) and oleic acid (OA) with a molar ratio about 1 : 1 acted as capping agent, the average size of the branched Pd NCs is about 37 nm (Fig.…”
Section: Common Strategies For Controllable Synthesis Of Polyhedral Pd Ncsmentioning
confidence: 99%